2022
DOI: 10.3390/bioengineering9110662
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells and MSCs-Derived Extracellular Vesicles in Infectious Diseases: From Basic Research to Clinical Practice

Abstract: Mesenchymal stem cells (MSCs) are attractive in various fields of regenerative medicine due to their therapeutic potential and complex unique properties. Basic stem cell research and the global COVID-19 pandemic have given impetus to the development of cell therapy for infectious diseases. The aim of this review was to systematize scientific data on the applications of mesenchymal stem cells (MSCs) and MSC-derived extracellular vesicles (MSC-EVs) in the combined treatment of infectious diseases. Application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 238 publications
(204 reference statements)
0
10
0
Order By: Relevance
“…Recent findings indicated that MSCs conduct immunomodulatory activity, associated with monocytes and regulatory T cells (Tregs) through the special cytokine-independent mechanism [58,[69][70][71]. AMSCs display more potential immunomodulatory effects than BMSCs, suggesting that AMSCs could serve as a better alternative for immunomodulatory therapy [54,69]. In comparison, HUC-MSCs have shown a minimal response to the allogeneic immune risk in vivo, regarding HUC-MSCs as a suitable therapeutic candidate [72].…”
Section: Immunomodulation Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings indicated that MSCs conduct immunomodulatory activity, associated with monocytes and regulatory T cells (Tregs) through the special cytokine-independent mechanism [58,[69][70][71]. AMSCs display more potential immunomodulatory effects than BMSCs, suggesting that AMSCs could serve as a better alternative for immunomodulatory therapy [54,69]. In comparison, HUC-MSCs have shown a minimal response to the allogeneic immune risk in vivo, regarding HUC-MSCs as a suitable therapeutic candidate [72].…”
Section: Immunomodulation Of Mscsmentioning
confidence: 99%
“…It has been reported that HP-MSCs exhibit a better engraftment and expansion and capacity compared with BMSCs [52]. In recent years, MSCs from other sources, such as AMSCs, HUCB-MSCs, HUC-MSCs, and HPMSCs, have received considerable attention due to better immunomodulatory characteristics and proliferation rate as compared to BMSCs [53,54]. MSCs can be identified by distinguishing a specific panel of positive cell surface antigens ( CD29, CD73, CD90, and CD105) and negative cell surface markers (CD14, CD11b, CD19, CD34, CD45, CD79α, and HLA-DR).…”
Section: Introductionmentioning
confidence: 99%
“…[33] Furthermore, the standardization of the MSC manufacturing process and the preservation of MSC viability were other problems demanding prompt solutions. [34,35] To overcome these shortages, several pioneers have tried combining the cell membrane of MSC with nanoparticles to structure a biomimetic drug vehicle for embracing the advantages of both nanoparticles and MSC. [36][37][38] For example, MSC membrane was applied to coat nanoparticles loading MSC secretions for fabricating an MSC mimic system.…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ] Furthermore, the standardization of the MSC manufacturing process and the preservation of MSC viability were other problems demanding prompt solutions. [ 34,35 ]…”
Section: Introductionmentioning
confidence: 99%
“…MSC-derived EV (MSC-EV) has been extensively studied and has demonstrated several promising effects, as reviewed by Gowen et al [ 10 ], Tieu et al [ 11 ], Fuloria et al [ 12 ], Kou et al [ 13 ], and Yudintceva et al [ 14 ]. However, despite the high potential of MSC-EVs, several factors limit their use.…”
Section: Introductionmentioning
confidence: 99%